Integrating biodiversity and livelihood improvement: The role of markets for mango varieties and garcinia species in India - Kruijssen, S.; Mysore, S. (2010)
The study described in the report was conducted to increase understanding of the role of markets in the maintenance of tropical fruit diversity on farm. The field study was conducted in southwest India and comprised three fruit species; mango, Garcinia indica (kokum) and Garcinia cambogia (uppage). A range of research methods was used in five study sites in Andhra Pradesh (commercial mango), Karnataka (homegarden and wild mango, kokum and uppage) and Maharashtra (more commercialized kokum) in order to identify the trends and status of target fruit diversity, assess the economic contribution of the fruits to the livelihoods of the households dependent on these species, to determine the status and contribution of markets (organised or unorganised) on fruit diversity and the influence of the existing policies on the collection, production, utilization and marketing of the species. Commercial mango diversity shows a declining trend with an increasing level of household income, while the level of education of the head of households is positively correlated with varietal diversity. While for commercialization, fruit traits related to production and marketing are essential, the important traits of fruits collected from homegardens and the wild are more related to their use for the household. In this report, four cases are presented and the collection, use and marketing of kokum and uppage are compared in different stages of commercialization. Factors that can increase the contribution of these fruits to household income while securing agrobiodiversity are: increasing consumer awareness of the uses of kokum and uppage; the establishment and strengthening of farmer organizations to increase efficiency and improve access to markets; the introduction of processing technologies and the development of new products; and at the same time the implementation of a conducive institutional and policy environment that supports the maintenance of diversity. The report recommends that more research is conducted on the production, market and use traits of tropical fruits, coupled with an increase in grower or collector (i.e. harvester from the wild) awareness about them. This may be achieved by the development, branding and promotion of products derived from locally-important agricultural biodiversity. The evaluation of the suitability for on-farm conservation for specific varieties and species is needed to assess which varieties and species are in general suitable to be conserved through on-farm measures and which would need to be conserved through ex situ methods in order to optimize genetic diversity conservation and minimize costs.